Study of a Far Infrared Cavity around an AGB Star under Iras Survey at Galactic Latitude -1.6° - Gautam, A. K.; Aryal, B. (Journal of Nepal Physical Society, 2019)
In this paper, we discuss about the physical properties of the dusty environment around the AGB star located at R.A. (J2000) = 06h 42m 02s and Dec (J2000) = 00° 53’ 00”, in the far infrared (60 and 100μm) IRAS maps. A cavity like structure (major diameter ∼ 2.5 pc & minor diameter ∼0.9 pc) is found to lie at R.A. (J2000) = 06h 41m 43.03s and DEC (J2000) = 01° 09’ 22.8”, located at a distance ∼ 405 pc from the star. By using contour map diagram, we studied the distribution of flux density, dust color temperature, dust mass and outflow mass in the cavity. The dust color temperature is found to lie in the range 21.4K to 21.9 K which shows the cavity is isolated and independently evolved. Such a low offset temperature variation shows that the star is stable and its life is long. Dust particles are less interacting and mean free path is large. The cavity may be in thermally pulsating phase. Product of dust color temperature and visual extinction is found to be less than one. A possible explanation of the results will be discussed.